Detection thresholds in audio-visual redirected walking - Florian Meyer and Malte Nogalski and Wolfgang Fohl (Zentrum fur Mikrotonale Musik und Multimediale Komposition (ZM4), Hochschule fur Musik und Theater, 2016)
Redirected walking is a technique that enables users to explore a walkable virtual environment that is larger than the extent of the available physical space by manipulating the users' movements. For the proper application of this technique, it is necessary to determine the detection thresholds for the applied manipulations. In this paper an experiment to measure the detection levels of redirected walking manipulations in an audio-visual virtual environment is described and the results are presented and compared to previous results of a purely acoustically controlled redirected walking experiment.
Keywords: Audio-visual; Detection levels; Detection threshold; Redirected walkings; Virtual reality